An electrochemiluminescence biosensor for Kras mutations based on locked nucleic acid functionalized DNA walkers and hyperbranched rolling circle amplification. Issue 20 (3rd February 2017) - Zhang, Ying; Wang, Lixu; Luo, Fang; Qiu, Bin; Guo, Longhua; Weng, Zuquan; Lin, Zhenyu; Chen, Guonan
Abstract : Herein, an electrochemiluminescence (ECL) biosensor for ultrasensitive and specific detection of Kras mutant genes has been developed. Abstract : Herein, an electrochemiluminescence (ECL) biosensor for ultrasensitive and specific detection of Kras mutant genes has been developed on the basis of the high discrimination capability of locked nucleic acid (LNA) and dual signal amplification techniques including DNA walkers and hyperbranched rolling circle amplification (HRCA).